Hypnobirthing Increase Pain Tolerance And Anxiety In Active Phase Labor - Nursalam Nursalam; Retnayu Pradanie; Ida Ayu Trisnadewi (Jurnal Ners, 2008)
Introduction: The main problem of inpartu mother was a labour pain and anxiety. The etiology of labour pain has been determained by dilatation and cervic’s tickness. The objective of this study was to examine the effect of hypnobirthing relaxation on the pain tolerance and anxiety responses in labor.Methods: A pre experimental static group comparison purposive sampling design was used in this study. Population were all pregnant women in age of pregnancies between 38 until 39 weeks at RSUD Wangaya Denpasar. There were 12 respondents who met to the inclusion criteria divided into 6 respondents were given hypnobirthing relaxation intervention and 6 respondents as the control group. The independent variable was hypnobirthing relaxation and dependent variables were tolerance of pain and anxiety responses. Data were collected by using observation and questionnaire, then data were analyzed by using Mann Whitney U Test with significance level p=0.05.Results: The result showed that hypnobirthing relaxation had an effect on the pain tolerance and anxiety responses (p=0.015.Conclusion: It can be concluded that the hypnobirthing relaxation has an effect to increase the pain tolerance and to decrease anxiety responses in active phase of labour. It is recommended to the hospital that have an ante natal care to hypnobirthing relaxation technique. Further studies should measure the effect of hynobirthing relaxation on increasing of β-endorfin in active phase labour.